Love is my savior : the Arabic poems of Rumi - Jalāl al-Dīn Rūmī, Maulana, 1207-1273 (Arabic literature and language series., 2016)
This new volume of Rumi's works, the first-ever English translation of his Arabic poems, will be exciting for the newcomer to Rumi's verses as well as to readers already familiar with his mystical philosophy. The poems take the reader on a journey of spiritual exploration, ecstatic union, cruel rejection, and mystic reconciliation. Rumi reveals his soul and welcomes everyone to his spiritual feast.